Milk production performance of Begait goat under semi intensive and extensive management in Western Tigray, North Ethiopia - Hagos, A.; Gizaw, Solomon; Urge, Mengistu (2018)
The study was conducted in Kafta humera district of Ethiopia, (i) to investigate the milk yield of Begait goat under different management and (ii) to evaluate the effects of different non-genetic factors on lactation performance. Data were collected from 428 lactating does under two managements (semi intensive and extensive) during October 2014 and March 2016. Statistical analyses were carried out using the GLM procedure of SAS version of 9.2 software. The least squares means (with standard error) for daily milk yield, lactation milk yield and lactation length were observed to be 0.75±0.01 kg, 85.6±1.04 kg and 111±1.21 days under semi intensive management, respectively whereas under extensive management these were found as 0.55±0.01 kg, 56±1.43 kg and 101±1.57 days, respectively. The results of this study indicated that management system, parity number and season of birth affected all variables highly significantly.